Temperature control using IBM/PC / Mohd Khairul Nizam Mat Noh, Ahmad Lutpi Ibrahim and Hanizar Hashim - Mat Noh, Mohd Khairul Nizam; Ibrahim, Ahmad Lutpi; Hashim, Hanizar (1990)
Control systems are used in. a great range of applications in the modern world, from household appliances to the most sophisticated guided missile system .Computers and particularly microprocessor based computers, are being applied in ever increasing numbers to all these areas of control. In this project a specialized type of control system will be studied for which all control inputs and outputs can be expressed in one of two conditions, ON or OFF. The use of an IBM/PC to provide control for this type of system will be studied. The two value nature of the variables in such systems makes interface to the computer particularly simple, but the control operations can still become quite complex.